2019
DOI: 10.2478/prilozi-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Importance of 6-Thioguanine Nucleotide Metabolite Monitoring in Inflammatory Bowel Disease Patients Treated with Azathioprine

Abstract: The active metabolite of azathioprine, 6-thioguanine nucleotide (6-TGN) is the main component responsible for the immunosuppressive effect in treatment of inflammatory bowel disease (IBD). The aim of this study was to assess the correlation between the concentration of 6-thioguanine nucleotide and disease activity, azathioprine-related adverse effects and time duration of treatment in patients with inflammatory bowel disease. Thirty-four patients were included in this study. Type of disease, gender, time durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…That observation was similar to that in another study [26]. On the contrary, Pavlovska et al reported a higher percentage of adverse effects [24]. The most common treatment-related complication was leucocytopaenia (42.9%), followed by elevated transaminase levels (28.6%), aphthous ulcers (14.3%), and elevated amylase in serum (14.3%).…”
Section: 3supporting
confidence: 87%
See 2 more Smart Citations
“…That observation was similar to that in another study [26]. On the contrary, Pavlovska et al reported a higher percentage of adverse effects [24]. The most common treatment-related complication was leucocytopaenia (42.9%), followed by elevated transaminase levels (28.6%), aphthous ulcers (14.3%), and elevated amylase in serum (14.3%).…”
Section: 3supporting
confidence: 87%
“…As in some other studies, we did not find any correlation between thiopurine dose and 6-TGN levels; therefore, increasing the drug dose may not be sufficient to reach the desired 6-TGN target [ 24 , 26 ]. This may be explained by an increased methylation of intermediate 6-MP metabolites by inherited high levels of TPMT activity [ 5 ].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It is well known that 6-TGN is the active metabolite responsible for AZA efficacy and cytotoxicity, and one of the side effects of AZA therapy is myelosuppression. Therapeutic drug monitoring (TDM) of one of the pharmacologically active metabolites of thiopurines, 6-TGN, has proven beneficial 36 . However, there is no unified conclusion about the relationship between the concentration of 6-TGN in red blood cells and adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) of the pharmacologically active metabolites of thiopurines, 6-TGN, has proven bene cial. 33 However, there is no uni ed conclusion about the relationship between the concentration of 6-TGN in red blood cells and adverse reactions. In the research of Asada et al 12 and Xiang Fei et al 29 , there was no statistically signi cant concentration difference observed between different NUDT15c.415C > T genotypes.…”
Section: Discussionmentioning
confidence: 99%